Development of a species-specific PCR-RFLP targeting rpoD gene fragment for discrimination of Aeromonas species - Puah, Suat Moi; Khor, Wei Ching; Kee, Boon Pin; Tan, Jin Ai Mary Anne; Puthucheary, Savithri Devi; Chua, Kek Heng (Microbiology Society, 2018)
Purpose. The taxonomy of Aeromonas keeps expanding and their identification remains problematic due to their phenotypic and genotypic heterogeneity. In this study, we aimed to develop a rapid and reliable polymerase chain reaction-restriction fragment length polymorphism assay targeting the rpoD gene to enable the differentiation of aeromonads into 27 distinct species using microfluidic capillary electrophoresis. Methodology. A pair of degenerate primers (Aero F: 5¢-YGARATCGAYATCGCCAARCGB-3¢ and Aero R: 5¢-GRCCDATGCTCATRCGRCGGTT-3¢) was designed that amplified the rpoD gene of 27 Aeromonas species. Subsequently, in silico analysis enabled the differentiation of 25 species using the single restriction endonuclease AluI, while 2 species, A. sanarelli and A. taiwanensis, required an additional restriction endonuclease, HpyCH4IV. Twelve type strains (A. hydrophila ATCC7966T, A. caviae ATCC15468T, A. veronii ATCC9071T, A. media DSM4881T, A. allosaccharophila DSM11576T, A. dhakensis DSM17689T, A. enteropelogens DSM7312T, A. jandaei DSM7311T, A. rivuli DSM22539T, A. salmonicida ATCC33658T, A. taiwanensis DSM24096T and A. sanarelli DSM24094T ) were randomly selected from the 27 Aeromonas species for experimental validation. Results/key findings. The twelve type strains demonstrated distinctive RFLP patterns and supported the in silico digestion. Subsequently, 60 clinical and environmental strains from our collection, comprising nine Aeromonas species, were used for screening examinations, and the results were in agreement. Conclusion. This method provides an alternative method for laboratory identification, surveillance and epidemiological investigations of clinical and environmental specimens.